Drama Korea Queen of Tears sebagai Soft Power Diplomacy dan Pendorong Perekonomian - Sari, Imelda (LPPM Institut Pendidikan Nusantara Global, 2025)
The aim of this research is to determine the extent to which Korea's cultural diplomacy has positive implications for improving the country's economy. This research examines cultural diplomacy using the drama Queen of Tears as the main example of the Korean Wave. The Korean Wave, also called Hallyu, emerged as South Korea's soft power that substantially improved its relations with various countries while encouraging economic growth. In 2004, the influence of Hallyu contributed to an increase in South Korea's GDP by 0.2 percent to reach 1.87 billion US dollars and in 2019 it increased to 12.3 billion US dollars. The Korean Wave has become a model of effective cultural diplomacy. A survey conducted in 2023 by the South Korean government showed that Indonesia ranked highest among 26 countries with a consumption level of Korean cultural content of 35.5 percent. This research uses qualitative research methods. The research results show that the use of culture that has strong support from the government, quality production and effective marketing strategies can contribute positively to improving bilateral relations, the tourism sector and the economy of a country.